The acute treatment fibrinogenopenia - Gonzáles del Riego, Manuel (2015)
In obstetrics the possibility of bleeding was and is always a common contingency. This accident, always fearful when gravity takes characters stains the box with tragic contours. Some obstetric complications are able to lead during its evolution, rebel cadres bleeding all usual treatment and having a common character that blood does not clot.